Patient-reported health-related quality of life from the phase III TOURMALINE-MM1 study of ixazomib-lenalidomide-dexamethasone versus placebo-lenalidomide-dexamethasone in relapsed/refractory multiple myeloma - Leleu, Xavier; Masszi, Tamas; Bahlis, Nizar J; Viterbo, Luisa; Baker, Bartrum; Gimsing, Peter; Maisnar, Vladimir; Samoilova, Olga; Rosiñol, Laura; Langer, Christian; Song, Kevin; Izumi, Tohru; et al. (American journal of hematology, 2018)
TOURMALINE-MM1 is a phase III, randomized, double-blind, placebo-controlled study of ixazomib plus lenalidomide and dexamethasone (IRd) versus placebo-Rd in patients with relapsed/refractory multiple myeloma following 1-3 prior lines of therapy. The study met its primary endpoint, demonstrating significantly longer progression-free survival (PFS) in the IRd arm versus placebo-Rd arm (median 20.6 vs 14.7 months, hazard ratio 0.74, P = .01), with limited additional toxicity. Patient-reported health-related quality of life (HRQoL) was a secondary endpoint of TOURMALINE-MM1. The European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core-30 (QLQ-C30) and Multiple Myeloma Module 20 (QLQ-MY20) were completed at screening, the start of cycles 1 and 2, every other cycle, the end of treatment, and every 4 weeks until progression. Over median follow-up of 23.3 and 22.9 months in the IRd and placebo-Rd arms, mean QLQ-C30 global health status (GHS)/QoL scores were maintained from baseline over the course of treatment in both groups, with no statistically significant differences between groups. EORTC QLQ-C30 function domain scores were also generally maintained from baseline; similarly, physical, emotional, and social function domains were maintained with IRd versus placebo-Rd, with slightly higher mean change from baseline scores at earlier time points with IRd. Findings from this double-blind study demonstrate that addition of ixazomib to Rd significantly improved efficacy while HRQoL was maintained, reflecting the limited additional toxicity seen with IRd versus placebo-Rd, and support the feasibility of long-term IRd administration.